The study of the relationship between parental involvement and early reading literacy development - Thanusha, Muniandy (2019)
Children who begin schooling with full literacy capability tend to perform better compared to children who are less exposed to early reading at home. Children who have lack of reading proficiency struggles to read, generally throughout schooling. Parent’s role is essential for children to experience faster and better literacy development. This study contains two purposes which was to examine the importance of parent’s involvement in children’s reading abilities at home and to examine and explore on the type of reading materials used by the parents to enable the children to foster interest in early reading. Therefore, this research study finalized the findings in the effectiveness of parent’s involvement in early literacy development with the usage of suitable reading materials. Three parents were selected and face-to-face interviews were carried out. Through the findings, the objectives were able to be achieved. The importance of parental enrolment into making their child a proficient reader has been highlighted by the parents themselves during the interviews that was conducted earlier. The parents have stated the reason for them to start reading early and they have also mentioned how early the readings were initiated. The parents have indicated that they started reading early because they were interested in reading and also because they have known about the strength of early reading and the benefits from it. Besides, the data have also revealed the reading materials the parents have used. Not forgetting, the suggestions from the parents about the reading materials to sustain a child’s motivations and interest for the continuous reading habits was also able to be examined. Parents shared the materials they used upon their kids like newspapers, books, posters and flashcards. In terms of recommendation on reading materials, parents have encourage the young parents to find books with colourful pictures, larger fonts and attractive pictures. They have also suggested the usage of internet in order to get more tremendous access of reading materials. The findings have proven that parent’s role is crucial in developing a child’s reading abilities. The parents were aware of their responsibility in choosing the proper reading materials. Therefore, the children were able to read constantly and were able to achieve good reading proficiency. The outcome from early literacy development was found to be a success. Parent’s initiative in providing assistance on their child’s literacy skills have found to be effective. This study as also concluded a positive relationship between the involvement of the parents and early literacy development. Therefore, this research study can be considered a very significant study as initiating reading habits at the young age will bring an awareness among the community and that will bring the society into a better place.